Conceptual approaches to the organization of a modern model of a consultative and diagnostic center on the principles of public-private partnership - V. V. Kravchenko (Kazimierz Wielki University, 2018)
Background The transition to progressive development models is an actual problem of the Ukrainian health care system. Objective: to substantiate conceptual approaches to the formation of a modern functional-organizational model of consultative-diagnostic centers (CDC) on the basis of public-private partnership (PPP). Materials and methods. General scientific methods of analysis, synthesis, generalization, interpretation of scientific data, as well as systemic and structural-functional approaches were used in the study. Results The article presents conceptual approaches to the organization of a consultative and diagnostic center on the principles of PPP, which include three components: the concept and methodological approaches to the restructuring of the CDC system, as well as the rationale for the organizational and economic formation of the CDC model on the principles of PPP. Conclusions Presented in the article the conceptual approaches to the organization of a modern model of a consultative and diagnostic center on the principles of PPPs are the way of adaptation of the communal CDC system to the conditions of a market economy.